Capital Structure and Firm Performance: A Comparative Study of Shariah-Compliant and Non-Shariah-Compliant Firms in Indonesia - Setiawan Setiawan (Indonesian Journal of Economics and Management, 2022)
This study seeks to examine the extent of influence of capital structure towards firm performance in shariah-compliant firms (SCFs) and non-shariah-compliant firms (NSCFs) in Indonesia. Data used are from the companies listed in Indonesian Stock Exchange. For SCFs, it was the companies listed in Jakarta Islamic Index and Sharia Stock Index while NSCFs are companies that not listed there. Data collected are 273 SCFs and 71 NSCFs. Data analysis using Mann Whitney, Panel Fixed Effects Regression and Generalized Methods of Moments. The result of this study shows that debt-financed capital structure in SCFs is smaller than NSCFs. Whereas firm performance in SCFs is higher than NSCFs. Another finding in SCFs is that Debt to Equity Ratio and Debt to Assets Ratio affecting Return on Equity, while Return on Assets only affected by Debt to Assets Ratio. The implication of this finding is that firm performance achievement in SCFs very much depends on its capital structure policy, so that the stakeholders shall be more careful to get into debt.